Effectiveness of care coordination interventions delivered to stroke survivors in low and middle-income countries: Systematic review and meta-analysis protocol - Stephanopoulos Kofi Junior Osei; Anthony Danso-Appiah (PLoS ONE, 2025)
Background Stroke survivors have complex and long-term care needs requiring navigation of multiple care services and providers. Care coordination interventions provide wholistic care that meets the needs of the patient and improves their clinical outcomes and expectations. This systematic review will identify the key components of stroke care coordination interventions implemented in low and middle-income countries (LMICs) and assess their effectiveness on stroke outcomes such as motor recovery, cognitive function, mental health, stroke type and the role of stroke severity, type, and the nature of the interventions in influencing these outcomes. Methods Electronic databases, trial registries and non-database sources will be searched for published and unpublished studies. PubMed, LILACS, CINAHL via EBSCOhost, Scopus, Web of Science Core Collection, Cochrane CENTRAL and Google Scholar will be searched from 2000 to 31st May 2025, without language restriction. Trial registries including the WHO International Clinical Trials Registry Platform (ICTRP) and Clinicaltrials.gov will also be searched. Grey literature including dissertations, preprint repositories and conference proceedings will be searched. The key search terms include “stroke”, “care integration”, “continuity of care”, “information exchange”, “patient-centred care”, “multidisciplinary care”, “case management” and “low and middle-income countries”, together with their alternative terms and synonyms, singular and plural forms and American and British spelling. Hand search of references of relevant studies will be carried out and experts in the field of stroke care coordination interventions will be contacted for their knowledge about any study missed by our searches. The studies will be collated in Rayyan and duplicates removed. Study selection will be done using a study selection flow chart developed from the pre-specified eligibility criteria defined by the PICOS elements (P ─ patient, I ─ intervention, C ─ comparator, O ─ outcomes and S ─study). Quality in the included studies will be assessed for risk of bias using the Cochrane Risk of Bias tool (version 2) for Randomized Controlled Trials (RoB 2) and ROBINS-I for Non-randomized Studies of Intervention. Data will be extracted using a pre-tested data extraction form developed from Microsoft Excel. Study selection, data extraction and risk of bias assessment will be conducted independently by two reviewers (SKJO and ADA). Disagreements between the reviewers will be resolved through discussion. Risk ratio (RR) will be used as the effect measure for binary/dichotomous outcomes. For continuous outcomes mean difference (MD) with standard deviation (SD) or standardized mean difference (SMD) for outcomes measured on different instruments or scales will be used as effect measures for expressing effectiveness of care coordination interventions. Random-effects meta-analyses will be employed to pool studies, and all effects estimates will be reported with their 95% confidence interval (CI). Heterogeneity will be assessed using the I2 statistic. The overall certainty of evidence will be assessed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE). Expected outcomes This review will attempt to identify the components of stroke-coordinated care interventions in low- and middle-income countries. It will assess whether these interventions improve clinical outcomes such as motor and cognitive functioning, mental wellbeing, mortality, and disability-adjusted life years (DALYs) of stroke survivors. The review will also explore how factors —such as stroke type, severity, and the nature of care coordination interventions (including the specific components) influence clinical, functional and psychosocial outcomes. The findings will help in determining the most effective care coordination interventions that should be adopted as care models to improve patient outcomes, whilst identifying evidence gaps for future research. Protocol registration and dissemination This systematic review and meta-analysis protocol has been registered in PROSPERO [CRD42024587311]. The findings of the study will be shared with the relevant stakeholders and disseminated through scientific conferences and peer review publications.